Heterologous expression and molecular characterization of the NAD(P)H:acceptor oxidoreductase (FerB) of Paracoccus denitrificans - Tesarík, Radek; Sedlácek, Vojtech; Plocková, Jana; Wimmerová, Michaela; Turánek, Jaroslav; Kucera, Igor (Protein expression and purification, 2009)
FerB is a flavoenzyme capable of reducing quinones, ferric complexes and chromate. Its expression in Escherichia coli as a hexahistidine fusion resulted in a functional product only when the tag was placed on the C-terminus. The molecular mass values estimated by gel permeation chromatography were compatible with the existence of either dimer or trimer, whereas the light scattering data, together with cross-linking experiments that yielded exclusively monomer and dimer bands on dodecyl sulfate-polyacrylamide gels, strongly supported a dimeric nature of both native and tagged form of FerB. These two proteins also exhibited almost identical secondary structure as judged by Fourier transform infra red spectrometry. The presence of tag, however, shifted the temperature of thermal inactivation as well as the thermal denaturation curve towards lower temperatures. Despite somewhat lower thermal stability, the fusion protein is considered a better candidate for crystallization than the wild-type one due to a more negative value of its second optical viral coefficient.
Keywords: Protein Multimerization; Calorimetry, Differential Scanning; Recombinant Fusion Proteins; Paracoccus denitrificans; Temperature; Protein Structure, Secondary; Oligopeptides; teplota; Histidine; Escherichia coli; sekundární struktura proteinů; Fourier Analysis; diferenciální skenovací kalorimetrie; oligopeptidy; NADH, NADPH oxidoreduktasy; histidin; NADH, NADPH Oxidoreductases; Enzyme Stability; Fourierova analýza; rekombinantní fúzní proteiny; NADP; stabilita enzymů; multimerizace proteinu